POTENSI DAN CABARAN TERHADAP PERLUASAN SUMBER ZAKAT SEKTOR PERTANIAN DI MALAYSIA - Sanep Ahmad; Hairunnizam Wahid; Wiyadi Wiyadi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2008)
Since the early Islamic period zakat on agriculture sectors were being collected limitedonly on primary traditional sources such as paddy, wheat, camel, cow and goat. However in themodern time today agriculture sector has been commercialized. Farmers regardless of theiractivities, were capable of yielding good returns probably higher than the traditional sourc es ofzakat. The question is, are these farmers not obliged to pay zakat and what is the possibility ofwidening zakat base on agriculture sector. In this regards this study attempts to examine thepossibilities of widening agriculture zakat base, and then evaluating people perception andanalyzing the challenges. This study utilizes primary data for Malaysia and uses descriptiveanalysis and logit model in analyzing the data. The results show that based on income criteriathere are possibilities to extend agriculture zakat base and this step is expected to received goodresponse from the society. However there are challenges to be faced such as identifying theillah for zakat on uncensunsus wealth and determining the procedure for calculating zakat onagriculture sector since different types of plants possess different characteristics. Policyimplication that can be deduced from this study is that in order to hinder any difficulties there isa need for the government to establishing a separate law for zakat on agriculture sector.